Pengaruh Kualitas Layanan Dan Harga Terhadap Loyalitas Pelanggan Melalui Kepuasan Pelanggan (Studi Pada Pelanggan Grab Bike Di Kalangan Generasi Z Surabaya) - Silmi Rahmani; R. Yuniardi Rusdianto (Journal of Economic, Bussines and Accounting (COSTING), 2024)
Transportation is needed to ensure the organization of mobility of people or goods. One of the public transportation that is often used is the motorcycle vehicle, which is often referred to as ojek. But in reality this service still has many shortcomings that its customers complain about, such as unsuitable service and prices. In resolving complaints and transportation problems, transportation service providers are needed who can meet and resolve these problems. Grab is an online transportation application widely used in Indonesia. This study is a study of a quantitative type. This study used the Gen Z population in the Surabaya area who are Grab Bike customers who have used the service more than twice, with the amount of data known through BPS being 877,427 data. In determining the sample is used purposive sampling.Information is collected by distributing a questionnaire to the respondents, that is, giving 20 questions. From the research we have obtained that the quality of service affects customer loyalty, price affects customer loyalty, customer satisfaction affects customer loyalty, quality of service affects customer loyalty, price affects customer loyalty, quality of service affects customer loyalty through customer satisfaction, and price affects customer loyalty through customer satisfaction.